Pear pomace soluble dietary fiber ameliorates the negative effects of high-fat diet in mice by regulating the gut microbiota and associated metabolites - Ji, Yuehong; Mao, Kemin; Gao, Jie; Chitrakar, Bimal; Sadiq, Faizan Ahmed; Wang, Zhongxuan; Wu, Jiangna; Xu, Chao; Sang, Yaxin (Frontiers in Nutrition, 2022)
The gut microbiota and related metabolites are positively regulated by soluble dietary fiber (SDF). In this study, we explored the effects of SDF from pear pomace (PP) on the regulation of gut microbiota and metabolism in high-fat-diet-fed (HFD-fed) C57BL/6J male mice. The results showed that PP-SDF was able to maintain the HFD disrupted gut microbiota diversity with a significant increase in Lachnospiraceae_UCG-006, Akkermansia, and Bifidobacterium spp. The negative effects of high-fat diet were ameliorated by PP-SDF by regulating lipid metabolisms with a significant increase in metabolites like isobutyryl carnitine and dioscoretine. Correlation analysis revealed that gut microbiota, such as Akkermansia and Lachnospiraceae_UCG-006 in the PP-SDF intervention groups had strong positive correlations with isobutyryl carnitine and dioscoretin. These findings demonstrated that PP-SDF interfered with the host's gut microbiota and related metabolites to reduce the negative effects caused by a high-fat diet.